Possibilities and constraints of rapid online ethnography: Lessons from a rapid assessment of COVID-19 policy for people who use drugs - Eaves, Emery R.; Trotter, Robert T.; Marquez, Bonnie; Negron, Kayla; Doerry, Eck; Mensah, David; Compton-Gore, Kate A.; Lanzetta, Shana A.; Kruithoff, Kathryn; Dykman, Kaitlyn; Baldwin, Julie A. (Frontiers in Sociology, 2022)
During the COVID-19 Pandemic, health care provision changed rapidly and funding became available to assess pandemic-related policy change. Research activities, however, were limited to contactless, online delivery. It was clear early on that some elements of online rapid ethnography were feasible and effective, while others would not approach traditional ethnographic depth. We conducted an online Rapid Assessment, Response, and Evaluation (RARE) project from August 2020 to September 2021 to understand how COVID-19 policy impacted people who use drugs. Our interdisciplinary research team conducted online ethnographic interviews and focus groups with 45 providers and community stakeholders, and 19 clients from rural and urban areas throughout Arizona. In addition, 26 webinars, online trainings, and virtual conferences focused on opioid policy and medication for opioid use disorders (MOUD) were opportunities to observe conversations among providers and program representatives about how best to implement policy changes, how to reach people in recovery, and what aspects of the changes should carry forward into better all-around opioid services in the future. Our RARE project was successful in collecting a range of providers’ perspectives on both rural and urban implementation of take-home MOUDs as well as a wide view of national conversations, but client perspectives were limited to those who were not impacted by the policies and continued to attend in-person daily clinic visits. We describe challenges to online rapid ethnography and how online research may have allowed for an in-depth, but incomplete picture of how policy changes during COVID-19 policy affected people with opioid use disorders.